Evaluation of relationship between disc position and morphology of Articular eminance of TMJ in MRI images of patients with TMD - Daryosh Goodarzipour; Allahyar Nezadi; Bahareh Purtaji; Yasaman Mohemkar Kheirandish (Tehran University of Medical Sciences, 2013)
Background and Aims: Because of high prevalence of TMJ dysfunctions , increased promotion of diagnostic and treatment methods is necessary. In many cases, in addition to disc position, morphology of other joint components such as articular eminence can be changed and therefore the probable correlation between disc position and morphology of hard tissue components can be used for prediction of internal derangements. The aim of this study was to evaluate the correlation between the position of disc and morphology of articular eminence of TMD`s patients using magnetic resonance imaging (MRI). Materials and Methods: In this cross sectional study by evaluation of digital MRI files, ultimately 78 joint images were identified which had sufficient quality and resolution for review. Then the MRI images, were observed and evaluated by 3 oral and maxillofacial radiologists to determine the disc position (normal, anterior displacement with and without reduction, and posterior displacement) and morphology of articular eminence (Box, Sigmoid, Flattened). Ultimately the results that were reported at least by 2 observers were included as the final results and were recorded in the check list. Data were analyzed using Chi-Square test and Fisher test. Results: In this study, no case of posterior disc displacement was found and therefore was excluded from the study. Articular eminence morphology (Flattened versus Sigmoid) showed statistically significant correlation with anterior disc displacement with and without reduction (P-values for anterior displacement with and without reduction were 0.03 and 0.002, respectively). No significant difference was found between the sigmoid and box types in relationship with disc displacement (P-values for anterior displacement with and without reduction were 0.72 and 0.70. In this study, no significant difference between the anterior disc displacement with reduction and anterior disc displacement without reduction in relationship with the morphological changes of articular eminence in any of the cases were found. Conclusion: The results showed that flattening of articular eminence had significant relationship with anterior disc displacement.